Management of receivables in Czech companies - Souček, Jiří; Kubíčková, Dana (Zarządzanie należnościami w firmach czeskich, 2011)
The management of receivables is an important component of corporate governance, but there is only little knowledge of the way small and medium-sized enterprises manage receivables in real practice: which system, methods, and forms they use for the management and the collection of receivables, how they secure their receivables. The research among the Czech companies carried out at the University of Finance and Administration in Prague brings some interesting findings. The main weaknesses are found in the selection and identification of solvency of business partners, the insufficient or none security of receivables, the insufficient co-operation with collecting agencies, or declining legal proceeding at debt collection. The results of this research are presented in the present article
Ekonomia = Economics, 2011, Nr 2 (14), s. 185-193
Keywords: receivables; management of receivables; debt collection; solvency